PERAN MANAJEMEN KEUANGAN DALAM PENGELOLAAN UMKM UNTUK MENINGKATKAN KEBERLANJUTAN BISNIS - Sholeha, Alfiatus; Afia Nurafifah; Isra Misra (Fakultas Ekonomi dan Bisnis Islam Institut Pesantren Sunan Drajat Lamongan, 2025)
This study analyzes the role of financial management in the management of MSMEs to support business sustainability. Using a descriptive qualitative method based on literature studies, this study collects data from various reliable literature during the period 2017–2024. The focus of the research includes financial management strategies such as transaction recording, cash flow management, the use of technology, and financial literacy. The results show that good financial literacy and the application of modern technology greatly affect the efficiency and sustainability of MSMEs. Proper financial management helps MSMEs overcome challenges such as access to capital, financial records, and cost efficiency. Support from the government through the Kredit Usaha Rakyat (KUR) program and financial training is a strategic step to increase the competitiveness of MSMEs in the global market.